Tris(2-methylpiperidinium) tetrachloridoferrate dichloride - Xu, Qian (International Union of Crystallography, 2012)
The asymmetric unit of the title salt, (C(6)H(14)N)(3)[FeCl(4)]Cl(2), consists of a tetrahedral tetrachloroferrate anion, three independent 2-methylpiperidinium cations and two chloride ions. All the piperidine rings adopt chair conformations. In the crystal, the organic cations and the free chloride anions are linked into chains parallel to the a axis by N—H⋯Cl hydrogen bonds.